Taxation in relation to trusts: an introduction - Coetzee, Martin Edward (Department of Commercial Law, 2026)
While the focus of this paper is an introduction to taxation in relation to the Trust as established in South African Law today it is clear that tax law and legislation is extremely complex in its diverse application. It is accordingly beyond the scope of this paper to provide a detailed analysis of the current tax laws as applied to Trusts. It will first be necessary to briefly examine the origins of South African Trust Law and historic development through the authorities to present day.